Mental Health Literacy and Mental Health Information-Seeking Behavior in Iranian University Students - Mahmoodi, Seyed Mohammad Hossein; Ahmadzad-Asl, Masoud; Eslami, Mohammad; Abdi, Mohadeseh; Hosseini Kahnamoui, Yasamin; Rasoulian, Maryam (Frontiers in Psychiatry, 2022)
Background: Inadequate Mental health literacy (MHL) is a problem worldwide. Research is limited in developing countries and about positive MHL. Disease-oriented MHL and positive MHL are measured in this study, and their association is investigated. Also, mental health information-seeking behavior is explored. Methods: This analytical cross-sectional study recruited undergraduate students of Tehran public universities through multistage stratified random sampling. MHL was measured using Mental Health Literacy Scale (MHLS) and Mental Health Positive Knowledge (MHPK). Participants' most used mental health information sources and their trust in them were also inspected. Results: A total of 543 students participated. On average, they achieved about 65% of the total possible MHLS score, and 71% of participants showed sufficient MHPK score. The "internet" was the most used source for receiving and searching for mental health information. The most trusted source was "health care staff". No correlation was detected between disease-oriented MHL and positive MHL. Conclusions: Mental health literacy of Iranian students still seems to be insufficient. As disease-oriented MHL and positive MHL were not correlated, specific educational interventions for each domain are needed. Despite the importance of the internet as a source of students' mental health knowledge, little trust in it should be considered in designing such interventions.